Application of Chaetomium cochliodes CTh02 to against durian root rot cause by Phytophthora palmivora RT01 - Tongon, R.; Soytong, K. (International Journal of Agricultural Technology, 2021)
The durian is cultivated in tropical regions which are caused root rot by Phytophthora palimovora RT01. P. palmivora RT01 causing root rot of durian var. monthong was proved to be pathogenic isolate and confirmed morphological and phylogenetic identification. Chaetomium cochliodes CTh02 proved to be antagonized P. palmivora RT01 causing root rot of durain var. monthong through dual culture evaluation. Crude hexane, crude ethyl acetate and crude methanol extracts of Ch. cochliodes CTh02 significantly inhibited colony growth of P. palmivora RT01 at the ED50 values of 955, 402 and 240 ppm., respectively. Morevover, Crude methanol extracts gave significantly highest inhibited sporangia of P. palmivora RT01 which ED50 value of 25 ppm and followed by crude hexane, crude ethyl acetate extracts which the ED50 values of 163, and 339 ppm, respectively. The control mechanism Ch. cochliodes CTh02 against P. palmivora RT01 may possible act as antibiosis